2001
DOI: 10.1080/003655201750163213
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Increases the Severity of Acute Experimental Pancreatitis in the Rat

Abstract: Obesity had a negative influence on the outcome of necrotizing pancreatitis that was related to the magnitude of the pancreatic insult. The sodium taurocholate model in obese rats would be useful for future mechanistic studies of the effect of obesity on pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…Obesity was recently proposed as a risk factor for acute pancreatitis [16]. Furthermore, several studies have shown that obesity is strongly associated with the onset of complications and increased mortality in patients with acute pancreatitis [8,18], and a decreased survival rate has been reported in genetically obese Zucker rats following induction of experimental acute pancreatitis [25]. These results suggest that obesity could accelerate pancreatitis in WBN/Kob-fatty rats.…”
Section: Discussionsupporting
confidence: 51%
“…Obesity was recently proposed as a risk factor for acute pancreatitis [16]. Furthermore, several studies have shown that obesity is strongly associated with the onset of complications and increased mortality in patients with acute pancreatitis [8,18], and a decreased survival rate has been reported in genetically obese Zucker rats following induction of experimental acute pancreatitis [25]. These results suggest that obesity could accelerate pancreatitis in WBN/Kob-fatty rats.…”
Section: Discussionsupporting
confidence: 51%
“…Two meta-analyses [12,13] have indicated that obesity has relationships with the local complication rate, organ failure, and mortality. Moreover, in an animal study, obese rats were susceptible to severe pancreatitis [14]. Despite the many reports that relate obesity and severe pancreatitis, it is unclear why obese patients tend to get a more severe form of acute pancreatitis.…”
Section: Introductionmentioning
confidence: 98%
“…In patients with AP, a correlation between serum leptin and disease severity has been reported by some investigators but not by others (11,12). Although in animal models administration of leptin decreases AP severity (13)(14)(15)(16), more severe disease is present in leptin-deficient ob/ob and leptin receptordeficient db/db mice as well as leptin-receptor mutant fa/fa rats (17,18). However, the differential effect of obesity versus leptin deficiency has not been fully investigated.…”
mentioning
confidence: 99%